The Influence Of Work Productivity, Work Discipline, And Job Satisfaction On Kinerja Karyawan At Mas Al Asy'ariyah - Adinda Dwi Fanny; Desi Astuti; Yohny Anwar (Utan Kayu Publishing, 2025)
MAS Al Asy’ariyah. The research employs a quantitative approach with an emphasis on objective measurement through numerical data, statistical analysis, and hypothesis testing. The sampling technique used is saturated sampling, as the population consists of only 35 individuals, making the entire population the sample. MAS Al Asy’ariyah is a private Islamic senior high school established on October 12, 2016, in Sunggal District, Deli Serdang Regency. The results of the study indicate that Work Productivity has an influence on Kinerja Karyawan (t-count = 1.851 t-table = 1.661). Work Discipline does not influence Kinerja Karyawan (t-count = 1.581 t-table = 1.661). Job Satisfaction has a significant influence on Kinerja Karyawan (t-count = 2.285 t-table = 1.660). The R Square value of 0.607 shows that Work Productivity, Work Discipline, and Job Satisfaction simultaneously contribute 60.7% to Kinerja Karyawan, while the remaining 39.3% is influenced by other factors outside this study